Development of Pegalinu Media in Digital Literature Capabilities and Numeration Basic Third-Grade in Elementary School Gugus Wibisono, Jati District, Kudus Regency - Budiningtyas, Ade Kalpika; Fajrie, Nur; Utaminingsih, Sri (ICCCM Journal of Social Sciences and Humanities, 2023)
This study aims to analyze needs and develop products through the game in third-grade elementary school. The learning media developed are media through Android applications that can be operated using computers, androids, and gadgets offline or online. In addition, the Development of game literacy and numeracy games in digital literacy and basic numeracy skills for third-grade elementary schools in the Wibisono cluster, Jati District, Kudus Regency. This research is a research development or Research and Development (R&D) using the Borg and Gall development method, which aims to develop android-based learning media in thematic learning by paying attention to three quality aspects: valid, practical, and effective. Data analysis consists of qualitative data and quantitative data. Qualitative data was used to analyze how the responses of teachers and students in carrying out thematic learning using the android-based Pegalinu media. Meanwhile, quantitative data analysis was used to analyze the data collected from the questionnaire. Based on the results of interviews, questionnaires, and observations, the level of learning media needs for literacy and numeracy games in the form of games android-based. The results of this media development have been tested for effectiveness with the results of accumulated scores by three material validators, namely 53,52,52 from a maximum score of 60. An average of 87% of material expert validators was obtained. The accumulation of 3 validators of media experts, namely 63.70 and 71, from a maximum score of 80, obtained an average percentage of 85%. The accumulation of expert users is 15,16,17 from a maximum score of 20, obtaining an average percentage of 80%. So that all three are included in the "Very Eligible" criteria. Feasibility is also supported by student and teacher questionnaire responses, which show an average percentage of 80.97% and 86.28%, with the criteria of "Good" and "Very Good." Based on the results of the T-test, it was found that t count > t table, i.e., 4,822 > 1,674, it can be concluded that there is a significant difference between the experimental group and the control group. So, Pegalinu media is effective in digital literacy and basic numeracy skills for third-grade in elementary schools in the Wibisono sub-district. Jati Kudus Regency.